Directions for navigating the west-coast of Newfoundland [electronic resource] : with a chart thereof, and a particular account of the bays, harbours, rocks, sands, depths of water, latitudes, bearings and distances from place to place, the flowing of the tides, &c., from an actual survey, taken by order of Commodore Pallisser, governor of Newfoundland, Labradore, &c. - Cook, James, 1728-1779. (London : Printed for the author and sold by J. Mount and T. Page ., 1768)
Electronic reproduction. Mode of access: Internet. 44